Assessment of Gonadal Function Following Single Dose of Radioiodine Therapy in Differentiated Thyroid Cancer Patients of Reproductive Age - Chowdhury, Md Sunny Anam; Sultana, Sadia; Awal, Md Abdul; Sarmin, Suraya; Salekin, Mohammad Simoon (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: This interventional study has undertaken to assess the gonadal function of differentiated thyroid cancer (DTC) patients within reproductive age group following single dose of radioactive iodine (131I) therapy/ablation. Patients and Methods: A total of 69 patients (25 male and 44 female) of DTC were included in this study, those were referred for 131I ablation after total thyroidectomy. Following RAI, these patients were followed-up three times at three months interval. The usual I-131 dose was 75 or 100 m Ci for ablation of thyroid residues and 150 mCi for treatment of nodal metastasis. All the patients were interviewed about menstrual (female only) and reproductive history and investigated of the level of follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone of male patients and FSH, LH, estradiol (E2) of female patients before administration of 131I and three, six and nine months after therapy. Result: In this study all of the 25 (100.0%) male patients showed high FSH level after three months of therapy. The mean± SD FSH level of male patients was found significantly (p-0.001) higher (15.59±7.53 IU/L) after three months of therapy than the pretherapy (4.85±2.57 IU/L) level. The mean± SD of FSH level was significantly declining in six months and nine months of follow up. The mean± SD of LH hormone level of these patients was found 6.1±3.67 IU/L in pretherapy which was significantly increased to 7.67±4.33 IU/L after three months. The mean LH level was 7.20±3.98 IU/L at six months follow up and 7.3±3.5IU/L after nine months. The differences of LH level between 3 months to 6 months and 6 months to 9 months are not statistically significant. No significant change was observed in testosterone level throughout the study period. In female, five patients developed irregular menstruation (changed duration of cycle or lighter amount), three patients developed amenorrhea associated with hot flashes within six months of 131I administration. Biochemical study of the patients with amenorrhoea showed markedly elevated serum FSH, LH level and declined E2 level. The FSH, LH levels of the two patients with amenorrhea became normal within study period and one patient had persistent amenorrhea at 9 months. E2 level raised slowly. Conclusion: A single dose of radio-iodine (131I) therapy causes impairment of gonadal function of male patients within reproductive age group. In case of female patients the effect is insignificant. The effect is usually reversible and gonadal function of the patients restores within the study period. Bangladesh J. Nuclear Med. 19(2): 92-97, July 2016